2018
DOI: 10.1186/s13195-018-0421-8
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of cognitive function in middle-aged and elderly Chinese adults—findings from the EMCOA study

Abstract: BackgroundThe principal aim of this study was to demonstrate the gender-specific cognitive patterns among middle-aged and elderly Chinese adults, investigate the risk factors on global and domain-specific cognitive performance in men and women, respectively, and report demographically adjusted norms for cognitive tests.MethodsThe Effects and Mechanism of Cholesterol and Oxysterol on Alzheimer’s disease (EMCOA) study enrolled 4573 participants aged 50–70 years in three Chinese cities. All participants underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 56 publications
2
16
0
1
Order By: Relevance
“…Participants between the ages of 50 and 70 years were selected from a large-scale community-based study entitled the Effects and Mechanism investigation of Cholesterol and Oxysterol on Alzheimer’s disease (EMCOA) study, an ongoing multicenter epidemiological survey funded by the State Key Program of National Natural Science Foundation of China [20]. This study was registered at the Chinese Clinical Trial Registry as ChiCTR-OOC-17011882.…”
Section: Methodsmentioning
confidence: 99%
“…Participants between the ages of 50 and 70 years were selected from a large-scale community-based study entitled the Effects and Mechanism investigation of Cholesterol and Oxysterol on Alzheimer’s disease (EMCOA) study, an ongoing multicenter epidemiological survey funded by the State Key Program of National Natural Science Foundation of China [20]. This study was registered at the Chinese Clinical Trial Registry as ChiCTR-OOC-17011882.…”
Section: Methodsmentioning
confidence: 99%
“…A similar conclusion has been arrived by Li and Singh 20 : elderly women displayed faster rate of cognitive decline and more severe cognitive deterioration than elderly men. Additionally, closely related with our study population, An et al 21 inspected the cognitive patterns among the middle-aged and elder Chinese people, specifically considering sex differentiation. They reported that females tend to have verbal memory advantages over their male counterparts independent of age.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, males tend to have more intact cognition in general, with better functions in attention, execution, and processing speed. The disparities in cognition exhibited between the two sex groups have not been fully disclosed, but are considered to be the aftermath of differences in years of educations among that generation of the elderly Chinese population 19,21 .…”
Section: Discussionmentioning
confidence: 99%
“…A two-stage case-control study design was performed for metabolomic analyses: an initial discovery batch (MCI = 75; Control = 70) to identify free oxysterol pro les for MCI diagnosis, which were further validated in the validation batch (MCI = 178; Control = 178). Both MCI cases and controls were from the same source population of the EMCOA study, a prospective, multicenter, observational cohort study of cognitive health in middle-aged and elderly Chinese aged 50-70 years [23]. Demographical information, medical history of chronic diseases, a broad range of neuropsychological tests and dietary surveys of all participants were collected.…”
Section: Study Design and Populationmentioning
confidence: 99%